Does Low Price-Earnings Multiple Fetch Higher Scrip Returns in India? - Chatterjee, Ansuman; Sahoo, Prasant Kumar (Indian Journal of Finance, 2012)
The study investigates the relationship between the Price-Earnings multiple and the scrip returns in India. A sample size of 80 companies comprising of 8 different industries listed in Bombay Stock Exchange were taken up for a time period of 08 years from January 1st, 2001 to December 31st, 2008. Rather than a single holding period, the study considers multiple holding periods ranging from six months to four years. Eight different portfolios were constructed on the basis of the price-earnings of the scrips and their returns were compared. The study finds an inverse relationship between the price-earnings multiple and scrip returns, which levers up as the duration of the holding period increases. The variability of the scrip returns is explained to a greater extent by the linear relationship between the price-earnings and scrip returns during relatively longer holding periods (two to four years). It is also identified that the annualized returns of the low price-earnings based portfolios (value stocks) are greater than the high price-earnings based portfolios (glamour stocks) and the paired t test confirmed that the holding period duration of four or three years instead of six months or one year earn significantly higher annualized returns.